OH-10 Study of Inappropriate Antibiotic Usage in Poultry in East Nusa Tenggara - Diana A Wuri; Annytha Detha; Filomena Ramos; Desi Biru; Margie Meha; Anita Lakapu (Hemera Zoa, 2018)
INTRODUCTIONMisuse of antibiotics for livestock affects the health of livestock itself, such as resistance, treatment failure and also affect the food of animal origin (Yuningsih, 2005). Based on research on some traditional and modern markets in Kupang City showed that the presence of tetracycline residues in 2 chicken samples (Ngangguk et al., 2015). The purpose of this study was to determine the percentage of antibiotic use of poultry without prescription from veterinarians and the type of antibiotics often used in poultry in Kupang City, East Nusa Tenggara.